Pengaruh Financial Distress dan Komite Audit Terhadap Manajemen Laba Pada Sektor Pertambangan - Maya Mustika; Preztika Ayu Ardheta; Yudhistira Rannu Paembonan (Jurnal Ekonomi, 2020)
This study aims to determine the effect of Financial Distress and the Audit Committee on Earnings Management in mining sector companies listed on the Indonesia Stock Exchange (IDX). This study uses an associative research strategy with causality type and the data analysis method used is linear regression analysis of panel data with Eviews 10. The population of this study is all mining sector companies listed on the Indonesia Stock Exchange in 2016-2018. The sample was determined based on the purposive sampling method, so that a sample of 12 companies was obtained. The data collection method uses documentation through the official IDX website www.idx.co.id. Based on the results of linear regression analysis of panel data with a significance level of 5%, the results of this study conclude that: (1) Financial Distress has a significant effect on earnings management, (2) the Audit Committee has no significant effect on earnings management.